(untitled) (Ameghiniana, 2019)
A new genus and two new fossil species of continental gastropods from the upper part of the Irene Formation—which is probably Huayquerian–Montehermosian (early Pliocene) and is exposed in the Quequén Salado River (Buenos Aires Province, Argentina)—are described: the new genus and species of freshwater gastropod Argentisioliella pardignasi (Cochliopidae) and a new species of landsnail of the family Bulimulidae (Bocourtia (Kuschelenia?) bonariensis). Argentisioliella pardignasi is morphologically related to those described for the Pebas Formation of Pliocene age. The specimens have bulloid morphology, long and narrow aperture, with a channeled peristome and two folds in the columellar wall. This is the first description of similar snails of the Pebas and Irene formations. Bocourtia (Kuschelenia?) bonariensis is the most ancient record for the genus, being recorded far away from the area of its current distribution (northwest Argentina). The specimen is an internal cast, with more than three convex whorls and a large aperture. Its distribution would coincide with the final phase of the Mio–Pliocene climatic change, when numerous terrestrial gastropods of Patagonian and Pampean provenance disappeared. A well-conserved specimen of the terrestrial snail Austroborus (Strophocheilidae Pilsbry), showing an almost complete shell, with more than 4.5 convex whorls, last whorl and large aperture, was also recorded. In the study area, this genus was present during the Pleistocene and Holocene, living in restricted areas of Argentina and Uruguay, with a disjunctive and relictual distribution.